Theory of Phonon–Electron Interaction in Metals - S. M. Sichkar (Успехи физики металлов, 2017)
Ab initio calculations for h.c.p. metals are presented for the matrix element of electron–phonon interaction, Eliashberg function, and anisotropy of the transport function for the [101¯0] and [0001] directions. The theory takes into account the real shape of the crystal potential and its total variation due to excitation, which is caused by the presence of a phonon in the lattice. This approach allows going beyond the classical approach of the rigid-ions’ approximation and permits to take into account the anisotropy of the physical properties of crystals with non-cubic symmetry.